2D HILIC‐ELSD/UPLC‐Q‐TOF‐MS Method for Acquiring Phospholipid Profiles and the Application in Caenorhabditis elegans. Issue 2 (28th November 2021) - Sun, Xiaotian; Zhang, Tao; Zhao, Pinzhen; Tao, Guanjun; Liu, Ruijie; Chang, Ming; Wang, Xingguo
Abstract: Phospholipids are the main constituent of cellular membranes and have recently been identified to have diagnostic value as biomarkers for many diseases. Accordingly, much emphasis is now laid on developing optimal analytical techniques for the phospholipid profiles of various biological samples. In the present study, different classes of phospholipids are first separated by optimized hydrophilic interaction chromatography with evaporative light scattering detector (HILIC‐ELSD). The phospholipids in each class are then identified by ultraperformance liquid chromatography‐quadrupole time‐of‐flight mass spectrometry (UPLC‐Q‐TOF‐MS). Validation results confirm that this approach meets the requirements of quantitative analysis. Finally, the approach is adopted to analyze the phospholipid profiles in Caenorhabditis elegans . A total of 111 phospholipid species is identified according to the mass fragments. Major fatty acyl chains in phospholipids are found to be formed by oleic acid (C18:1), arachidonic acid (C20:4), and eicosapentaenoic acid (C20:5). Overall, this study improves current knowledge on analytical techniques of the phospholipid composition in C. elegans and provides a basis for future lipidomics research. Practical applications : Phospholipids reportedly play a crucial role in the development of many diseases. Until now, only a small portion of phospholipids in Caenorhabditis elegans has been reported by using one‐dimensional analysis strategy. The offline 2D liquid chromatography method developed in this study identifies 111 phospholipid species in Caenorhabditis elegans . The obtained phospholipid profiles complement the lipid database of Caenorhabditis elegans . The study also provides the basis for the future development of a 2D online approach. Abstract : A 2D hydrophilic interaction chromatography with evaporative light scattering detector (HILIC‐ELSD)/ ultraperformance liquid chromatography‐quadrupole time‐of‐flight mass spectrometry (UPLC‐Q‐TOF‐MS) method is developed to identify and quantify 111 phospholipid species in Caenorhabditis elegans .